Data for rate versus rhythm control strategy on stroke and mortality in patients with atrial fibrillation - Weng, Chi-Jen (Data Brief, 2018)
The data relates to the cohort of patients with atrial fibrillation (AF) from the National Health Insurance Research Database of Taiwan, “Rhythm Control Better Prevents Stroke and Mortality than Rate Control Strategies in Patients with Atrial Fibrillation - A Nationwide Cohort Study” (Weng et al., in press). The AF patients might receive either rate or rhythm control strategy according to the medication used. The baseline medication in rate and rhythm control groups was included in this dataset. Multivariate Cox hazards regression model was used to evaluate the hazard ratio (HR) for major adverse cardiovascular events (MACE), including ischemic/hemorrhagic stroke and mortality in AF patients receiving rate or rhythm control. The occurrence of MACE was identified from the ICD-9 CM codes. The data also contains the HR for MACE stratified by the CHA2DS2-VASc score, baseline characteristics, and the duration of strategy employed of the AF patients.